Environmental characteristics of 1 1/3 year old Acacia mangium stand. - Nuruddin, Ahmad Ainuddin; Deraman, Abdul Wahab (1989)
Establishment of forest plantation can affect the environment. This study was carried out to investigate the environmental characteristics of Acacia mangium stand. The study was conducted in a 1 1/3 year old A. Magnium stand in Rantau Panjang Forest Reserve. Environmental characteristics such as solar radiation, air temperature, relative humidity, and wind speed were taken. The data were taken hourly for five days and weekly for 18 weeks. The result showed that the forest floor received solar radiation of 175.5 W/m-2; 33.2°C with difference of 12.8°C between daily minimum and maximum temperatures, relative humidity with maximum of 99.6% and 76.6% minimum; wind speed maximum 15.3 m/sec. The soil temperature at 5cm depth differed by 0.6°C compared to 10 cm depth. The range of values for the parameters in the 1 1/3 year old stand were higher than those of natural forest stand.